CHANGING THE VECTOR OF EDUCATIONAL STRATEGIES IN TEACHING FOREIGN LANGUAGES AT THE UNIVERSITY: FROM LEARNING STRATEGIES TO STUDYING STRATEGIES (ResearchJet Journal of Analysis and Inventions, 2021)
To date, there is a need to review the approaches to the training of qualified specialists in higher education institutions. Of particular importance is the issue of students ' autonomy in learning a foreign language and their responsibility for the result of the study. Learning strategies will help students become more independent, increase their personal interest in learning, and teach them the processes of self-assessment and self-correction.